Evidence-based guidelines for resistance training volume to maximize muscle hypertrophy - Schoenfeld, B.; Grgic, J. (Strength and Conditioning Journal, 2018)
The manipulation of resistance training (RT) variables is widely considered an essential strategy to maximize muscular adaptations. One variable that has received substantial attention in this regard is RT volume. This paper provides evidence-based guidelines as to volume when creating RT programs designed to maximize muscle hypertrophy.